To solve the factored quadratic equation \((13x + 3)(9x - 14) = 0\), we will set each factor to zero and solve for \(x\):
-
Set the first factor to zero: \[ 13x + 3 = 0 \] \[ 13x = -3 \] \[ x = -\frac{3}{13} \]
-
Set the second factor to zero: \[ 9x - 14 = 0 \] \[ 9x = 14 \] \[ x = \frac{14}{9} \]
Now we have the solutions:
- \(x = -\frac{3}{13}\)
- \(x = \frac{14}{9}\)
The solution set is: \[ x = \left{ -\frac{3}{13}, \frac{14}{9} \right} \]
Looking at the provided options, the correct response is: The solution set is \( x = \left{ -\frac{3}{13}, \frac{14}{9} \right} \).